Syndrome of Undifferentiated Connective Tissue Dysplasia. Pulmonological Aspects - A.A. Konyushevskaya; M.A. Franchuk (Zaslavsky O.Yu., 2012)
The article deals with the problem of connective tissue dysplasia in children and the role of this pathology in the pathogenesis of diseases of the respiratory system. Etiologic aspects of the development of this pathology, classification, and specific clinical features of the course of some diseases against the background of connective tissue dysplasia in childhood are discussed.